Pilot randomized controlled trial testing the influence of front-of-pack sugar warning labels on food demand - Felicia Jia Ler Ang; Sagun Agrawal; Eric A. Finkelstein (BMC, 2019)
Abstract Background Front-of-pack (FOP) nutrition warning labels to identify potentially harmful foods/beverages have recently been considered in Singapore. The objective of this study was to pilot test two promising FOP warning labels intended to reduce purchases of products high in sugar to determine whether a full scale trial testing one or both these labels using actual purchases is warranted. Methods Five hundred twelve participants ≥21 years old and residing in Singapore completed all study elements online via the NUSMart Online Grocery Store study website. The study was designed as a Randomized Controlled Trial (RCT) where consumers were randomized and asked to hypothetically shop in one of three versions of an online grocery store; 1) no FOP label (control), 2) a graphical high-in-sugar label shaped like a stop sign, or 3) a text-based warning label. The proportion of labelled products purchased (primary outcome) and all secondary measures of diet quality were calculated using participants' orders. Ordinary Least Squares (OLS) regression was used to compare purchasing behavior across the three study arms. Results The proportion of high-in-sugar products selected (i.e., those targeted for labelling) was largest in the no label control arm at 20%. The proportion was a non-statistically significant 2 percentage points lower (P = 0.146) for the high-in-sugar stop-sign label arm and 4 percentage points lower (P < 0.05) in the warning label with deterrent text arm. We could not reject the hypothesis of equal effectiveness of the two warning labels (P = 0.231). Conclusions Results suggest that the two health warning labels have potential to reduce demand for high-in-sugar products in Singapore. Future studies should test the influence of these labels using actual purchases in efforts to identify whether either labelling strategy should be considered for adoption in the local setting. Trial registration The American Economic Association's registry for randomized controlled trials; AEARCTR-0003800. Registered 18 January 2019.